Puma predation subsidizes an obligate scavenger in the high Andes. Issue 3 (20th October 2016) - Perrig, Paula L.; Donadio, Emiliano; Middleton, Arthur D.; Pauli, Jonathan N.
Summary: The ungulate–carnivore–vulture complex is a key trophic module of many terrestrial ecosystems, but one that is globally under threat. Few have explored cross‐species dependencies in this module, and the degree to which vultures rely on trophic facilitation by apex carnivores is rarely known and almost never quantified. We investigated the importance of puma Puma concolor predation on its native camelid prey, vicuñas Vicugna vicugna and guanacos Lama guanicoe, in food provisioning for Andean condors Vultur gryphus in the high Andes of north‐western Argentina. We evaluated the origin of wild food sources through carcass surveys. We quantified condor feeding habits via foraging observations and through the analysis of pellet contents and stable isotopes from moulted feathers. Of the 102 fresh camelid carcasses we monitored, nearly all (94%) resulted from puma predation, and the majority (85%) of camelid carcasses used by condors were killed by pumas. Camelids represented 88% of the prey items identified from 183 condor pellets, and isotopic analyses of moulted feathers from 86 individuals identified via multilocus genotyping revealed that camelids and Small livestock were the most important prey items, representing 45–58% and 28–38% of condor assimilated biomass, respectively. Synthesis and applications . Our results show that puma predation plays a key role in the foraging ecology of Andean condors, and highlight the importance of predatory processes that make carrion available to scavengers. We contend that targeting the conservation of ungulate–carnivore–vulture modules, rather than a species‐specific approach, will be a more effective strategy to ensure the long‐term persistence of Andean condors and other obligate scavengers. Abstract : Our results show that puma predation plays a key role in the foraging ecology of Andean condors, and highlight the importance of predatory processes that make carrion available to scavengers. We contend that targeting the conservation of ungulate–carnivore–vulture modules, rather than a species‐specific approach, will be a more effective strategy to ensure the long‐term persistence of Andean condors and other obligate scavengers.